Post-vaccination Monitoring to Assess Foot-and-Mouth Disease Immunity at Population Level in Korea - Park, Mi-Young; Han, You Jin; Choi, Eun-Jin; Kim, HeeYeon; Pervin, Rokeya; Shin, Wonseok; Kwon, Doheon; Kim, Jae Myoung; Pyo, Hyun Mi (Frontiers in Veterinary Science, 2021)
In South Korea, domestic cattle, pigs, and goats were subjected to mandatory FMD vaccination and year-round sero-surveillance since 2011. In 2020, approximately USD 95 million were spent solely for FMD vaccine purchase for 59 million livestock and 1.25 million samples were tested to estimate population immunity and demonstrate the absence of virus circulation. As the FMD vaccination program was revised in 2018, the PVM was designed to evaluate effectiveness of the vaccine program of three vaccines approved for routine use. To this end, monitoring post-vaccination immunity has been conducted by collecting 35,626 serum samples at 28 day-post-vaccination (DPV) following regular national vaccinations, which were carried out in April and in October in 2020. The design of serological test for PVM was specially targeted at particular livestock groups, including dairy cattle, goats and beef cattle aged 6-12 months, which were generally estimated to have low expected seroprevalence. Also, the risk factors had been identified considering increased likelihood of infection in particular location, herd-size and husbandry system and applied in targeted sample collection. Serum sample collection and SP-O and NSP antibody tests were performed by local veterinary laboratories using commercially available ELISAs. Current FMD vaccination program which was performed twice a year following the regimen of primary vaccination and boost resulted over 80% of the population immunity. Seroprevalence monitored after the vaccination in fall was higher than the one studied in spring except in pigs. It was demonstrated that seroprevalence of risk based targeted samples ranged from 93.8 to 100% in cattle, 63.2 to 100% in pigs and 20.0 to 100% in goats. Of note that area near the North Korean borders showed relatively low seroprevalence among the targeted regions and no NSP sero-positive reactor was detected in this region. When sub-population immunity at individual level was assessed, seroprevalence in young cattle stock was slightly lower (95.8%) than that of adults (98.4%). In conclusion, FMD vaccination campaign has been successfully implemented in Korea and the PVM can be supplementary program for massive routine surveillance in terms of providing timely information needed both to estimate population immunity and to properly target ‘risk-based surveillance’.